Degradation kinetics, pathways, transformation products, and toxicity assessment of fluorochloridone in agricultural soils - Dong Zhao; Hongyu Chen; Shuo Shen; Enyu Lu; Junlong Feng; Hui Zhi; Lei Wang; Wei Li (Ecotoxicology and Environmental Safety)
Flurochloridone (FLC) is a pyrrolidone herbicide used to control broad-leaved weeds in various crop fields. However, there is still a lack of comprehensive research on the environmental fate of the Qinghai-Tibet Plateau (QTP) and the toxicity of its potential transformation products (TPs). In this study, laboratory experiments were conducted to investigate the degradation kinetics, pathways, and toxicity of FLC’s TPs. Nine TPs were identified in soil using Ultra-Performance Liquid Chromatography Quadrupole-Orbitrap Mass Spectrometry (UPLC-Q-Exactive Orbitrap MS) and Compound Discoverer software, employing suspect and nontarget screening strategies. The initial report of two TPs, TP204, and TP191 was confirmed through the acquisition or synthesis of their standards. High Performance Liquid Chromatography coupled with Tandem Mass Spectrometry (HPLC-MS/MS) was subsequently used for further quantification of these TPs in all samples under examination. The primary transformation reactions of FLC in the environment include oxidative dechlorination, reductive dechlorination, reductive defluorination, acetylation, and hydrolysis. Predictive assessments via ECOSAR, alongside empirical laboratory experiments, revealed that most novel TPs exhibit significantly lower acute toxicity towards Danio rerio, Daphnia magna Straus, and Algae compared to FLC. However, TP204 demonstrated neutral chronic toxicity towards Daphnia magna Straus and Green algae, potentially posing a latent threat to aquatic ecosystems. These results are crucial for elucidating the environmental fate of FLC, assessing environmental risks, and guiding scientific and reasonable use. This research holds significant importance for the ecological environment protection in the Tibetan Plateau region.